Isolation and identification of fungi from two hospitals in Baghdad city and effect of disinfectants on some fungi - R. Mohammed, Sadiq; H. AL-Jibouri, Mona (Iraqi Journal of Science, 2023)
Swabs from two hospitals at Baghdad city were collected from the period 28-October-2013 to 31-March-2014, to found out the prevalence and distribution of fungi. These isolates were collected from hospitals’ environment and most of the items used for hospital work in order to detect the nosocomial pathogens persistent. All fungal isolates were identified depending on the morphological and microscopic examinations as well as biochemical tests. Out of 220 environmental samples, 146 fungal isolates was obtained, Aspergillus flavus was more frequency and occurrence 23.29% and 15.45% respectively, followed Aspergillus niger was 15.57% and 10.45% then Penecillium spp. was 13.27% and 8.64%. In Al -Yarmouk Teaching Hospital more places contamination was burns 75%, followed dialysis 72.72% then RCU units 69.23%, while more places contamination in Imam Ali General Hospital was wards 70%, followed burns and Kitchen 58.33% then operation hall 57.14%. Determining the minimum inhibitory concentration for five types of disinfectants which are used in hospitals, the MIC values of disinfectants against fungal isolate were Chlorhexidin 7.5%, Chloroxylenol 1.25%, Formaldehyde 1.25%, Povidine iodine 10% and Sodium hypochlorite 7.5%. Chloroxylenol had significantly the most effective compound on fungi, followed formaldehyde then Sodium hipochlorite. This study found that hospitals contain different fungal species and genus, antiseptics and disinfectants have an effect on the fungus if it used correctly and permanent change in the use of antiseptics and disinfectants to avoid resistance of fungi.